Numeric evaluation of the stiffness of log-concrete composite beams submitted the cyclical load - Molina, Julio Cesar [UNESP]; Calil Junior, Carlito (Univ Politecnica Catalunya, 2010)
In this paper was evaluated, using the software ANSYS, the stiffness (El) of the log-concrete composite beams, of section T, with connectors formed by bonded-in steel rods, type CA-50, disposed in X, with application of cyclical load. The stiffness of the system was evaluated through the simulation of bending tests, considered 1/2 beam, with cyclical shipment varying among 40 % and 5 % of the strength of the connection with the load relationship R=0,125, for a total of 10 load cycles applied. The numeric results show a good agreement with experimental tests.